Satellite cell content in Huntington’s disease patients in response to endurance training - Mueller, Sandro Manuel; Mihaylova, Violeta; Frese, Sebastian; Petersen, Jens A.; Ligon-Auer, Maria; Aguayo, David; Flück, Martin; Jung, Hans H.; Toigo, Marco (Orphanet journal of rare diseases, 2019)
Background Skeletal muscle wasting is a hallmark of Huntington’s disease (HD). However, data on myocellular characteristics and myofiber remodeling in HD patients are scarce. We aimed at gaining insights into myocellular characteristics of HD patients as compared to healthy controls at rest and after a period of increased skeletal muscle turnover. Methods Myosin heavy chain (MyHC)-specific cross-sectional area, satellite cell content, myonuclear number, myonuclear domain, and muscle fiber type distribution were determined from vastus lateralis muscle biopsies at rest and after 26 weeks of endurance training in HD patients and healthy controls. Results At the beginning of the study, there were no differences in myocellular characteristics between HD patients and healthy controls. Satellite cell content per MyHC-1 fiber ( P = 0.014) and per MyHC-1 myonucleus ( P = 0.006) increased significantly in healthy controls during the endurance training intervention, whereas it remained constant in HD patients ( P = 0.804 and P = 0.975 for satellite cell content per MyHC-1 fiber and myonucleus, respectively). All further variables were not altered during the training intervention in HD patients and healthy controls. Conclusions Similar skeletal muscle characteristics between HD patients and healthy controls at baseline suggested similar potential for myofiber remodeling in response to exercise. However, the missing satellite cell response in MyHC-1 myofibers following endurance training in HD patients points to a potential dysregulation in the exercise-induced activation and/or proliferation of satellite cells. In the longer-term, impaired myonuclear turnover might be associated with the clinical observation of skeletal muscle wasting.